Low - Cost Strategy in Air Transport of Passengers - Krajnović, Aleksandra; Bolfek, Berislav; Nekić, Nikolina (Oeconomica Jadertina, 2017)
In recent years, in almost all of the markets, low cost airlines dedicated to the air transportation of passengers were established, presenting different business strategies if compared to the classical, national airlines. The term low-cost company is used in the aerospace industry indicating airlines that operate with lower operating costs, unlike their competitors. The success of low-cost airlines can be attributed to the low-cost dominantly positioned strategy adopted by the airlines. The main goal of this paper is focused on the analysis of selected cases of low-cost airlines and their comparison to traditional air carriers. Additionally, the purpose of this paper is to analyze low-cost airlines, comparing their characteristics with other segments of air traffic, identify their strategies, and identify the activities of the value chain that affect the most the reduction of costs
Keywords: low-cost strategy; value chain; low-cost airline model; the strategy of low-cost airlines; the market of low-cost airlines